2016
DOI: 10.1021/acs.energyfuels.5b02576
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Large Polycyclic Aromatic Hydrocarbons. Part 2: Solvent-Separated Fractions of Coal Tar Pitch and Naphthalene-Derived Pitch

Abstract: Complex polycyclic aromatic hydrocarbon (PAH) mixtures separated from a coal tar pitch (CP) and naphthalene pitch (NP) by sequential extraction with heptane and toluene were characterized in detail by applying a multiarray analytical approach. Gas chromatography–mass spectrometry (GC-MS), size exclusion chromatography (SEC), laser desorption ionization-time-of-flight mass spectrometry (LDI-TOFMS), and thermogravimetry (TG) were used to relate the volatility and coking yield of pitch components to their solubil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 45 publications
1
54
0
Order By: Relevance
“…Briefly, Iar is the aromatic hydrogen index, and CH 3 /CH 2 ratio is the aliphatic side chain index, obtained from the ratios of integrated absorbance peak areas. CH 3 /CH 2 can be considered as an estimate of the length of aliphatic chains of spinnable pitch . The calculation method can be described as follows: Iar=Abs×30500.5emcm1/()Abs×30500.5emcm1+Abs×29200.5emcm1 CH3/CH2=Abs×29500.5emcm10.5emband/Abs×29200.5emcm10.5emband …”
Section: Resultsmentioning
confidence: 99%
“…Briefly, Iar is the aromatic hydrogen index, and CH 3 /CH 2 ratio is the aliphatic side chain index, obtained from the ratios of integrated absorbance peak areas. CH 3 /CH 2 can be considered as an estimate of the length of aliphatic chains of spinnable pitch . The calculation method can be described as follows: Iar=Abs×30500.5emcm1/()Abs×30500.5emcm1+Abs×29200.5emcm1 CH3/CH2=Abs×29500.5emcm10.5emband/Abs×29200.5emcm10.5emband …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is noticeable that the absorption decrease for organic carbon is not as steep as in the case of standard PAH. This is shown in Figure 5 where the spectra of bulk particulate, soot and organic carbon fractions are contrasted with the spectra of two-to seven-ring standard PAH mixture (<300 u, < 24 C atoms), and large PAH (>300u, >20-24 C atoms) featuring the heptane-soluble (200-500 u) and toluene-soluble fractions (300-700 u) of a coal tar pitch (CP) [64]. In comparison to small-and medium-size PAH the broadening and shift at lower energy of the band edge for the organic carbon lead to the presumption of the presence of PAH aggregates [73].…”
Section: Organic Carbon B Sootmentioning
confidence: 99%
“…While the treatment for lung cancer has been greatly improved, the 5‐year average survival rate of lung cancer patients was still low . Coal tar pitch (CTP), a by‐product in the smoking process, is a crude material used in paint, rubber, synthon, medication, and heat‐resistant materials . And it has been confirmed that CTP extract constitutes polycyclic aromatic hydrocarbons (87.91%) and the remaining (12.09%) including monocyclic aromatic hydrocarbons, heterocyclic compounds and alkenes using gas chromatography/mass spectrometry .…”
Section: Introductionmentioning
confidence: 99%